The New School in the interior of Ceará: challenges faced by the reform of Lourenço Filho in the city of Sobral - Silva, Amanda Teixeira da (Temporalidades, 2019)
Justiniano Serpa, governor of the state of Ceará undertook, in 1922, a reform in the education of the state. The pedagogue from São Paulo, Lourenço Filho, who would later become one of the signatories of the Manifesto dos Pioneiros da Educação Nova, was the intellectual responsible for the so-called Reforma Serpa, which sought at the same time to democratize access to primary education and implement a new method of teaching in the state. The purpose of this work is to investigate the discourses and practices surrounding the implementation of the reform in the municipality of Sobral, located in the northern region of Ceará, between 1922 and 1932.  We discussed here, through local newspapers of that period, the reception of new educational ideals within the state of Ceará, as well as the practical problems that, over ten years, constituted obstacles to the practice of active teaching.